The influence of virtual communication towards responsiveness in manufacturing community - Yong, Jee Chong (2013)
With the rapid development of Information Communication Technology, many types of virtual communication channels are available to the employees. Email has been commonly used by the manufacturing community for virtual communication due to disparity of locations and time constraint. Responsive delivery of job with short cycle time requires zero waste information flow. Therefore, effective communication is essential for time-based job performance to keep a manufacturing company competitive. Additionally, effective communication has the mediating influence in the relationship between job satisfaction and behavioural intentions towards job accomplishment. Therefore, the relationship of communication satisfaction and job performance is crucial and need to be investigated. This experimental study was conducted to examine the responsiveness of job performance induced with time pressure by using email communication. Results show that email is a moderately effective communication channel for assigning job to a group of virtual workers, in some cases for repetitive and organized jobs that could not be completed within 24 hours. Quantitative analysis was also conducted to measure satisfaction level of communication using email as perceived by virtual workers towards performance of completed job. The relatively high in perceived communication satisfaction showed that email is effective in collaborative aspects of work. The communication satisfaction factors of communication climate and relation with superior could be enhanced by the organization in order to increase employees’ job performance